The Design of Data Collector to Calculate the Efficiency of DC to AC Inverter Based on ATmega328 and Micro SD as Storage Media - Brahmana, Kurnia (Journal of Technomaterial Physics, 2020)
The data collector to calculate the efficiency of the pure sine inverter DC to AC based on the level of efficiency, voltage and current stored automatically in Micro SD has been successfully designed. This data collector is built from the Arduino Nano (ATmega328) module as the controller and uses a Micro SD Card as a storage medium. The equipment storage results are displayed in real time using the RTC and LCD as a display medium for the measurement results of the voltage sensor and current sensor. The data logger is designed to be useful for storing data from the measurement results of the DC to AC inverter which consists of voltage, current and data collection time. The data every 16 seconds will be stored automatically on the Micro SD. The results of the reading error of the voltage sensor and current sensor are 1.088% and 1.72%, respectively. The results of the error reading the voltage sensor and current sensor are still precise, so the efficiency obtained in this study is 78.37%.